Le basi psicologiche della guerra e i rimedi per la pace in Hobbes e Kant - Mori, Luca (Filosofia, 2023)
In 1932, Albert Einstein asked Freud for a way to free humanity from war, stating that no attempt had yielded anything. This article attempts to draw some elements from Hobbes and Kant to answer Einstein’s question. The two philosophers provide various reasons for conceiving peace and war not in dichotomous terms, but as always coexisting polarities – in variable proportions – in the continuum of possible human interactions. In the philosophical perspective outlined here, given the fundamental ambiguity of human beings, there is no exhaustive and definitive answer to Einstein’s question. Following Hobbes and Kant, what can be achieved is not the elimination of any possibility of war, but the progressive improvement of understanding the measures that allow for the reduction of the probability of open hostility among individuals, groups, and States.